Modeling and prediction of performability of safety critical computer based systems using Petri nets - Singh L.K.; Vinod G.; Tripathi A.K. (My University, 2025)
Computer based safety critical systems are progressively replacing analog systems in safety-critical applications like nuclear power plants. Hence these systems require modeling techniques to estimate performability in the early stages of the system development life cycle. This paper addresses the dynamic modeling of Test Facility of a safety critical system used in Nuclear Power plant. System function and its architecture have been explained. No details of the system have been shown that can jeopardize the confidentiality & hence exact details have been concealed. Special attention has been paid to the modeling part of a communication module of this system in between the two computer based subsystems that are running on different platform, VxWorks and Linux, using a mathematical formalism, Petri Net. Also, formalism of Petri nets with particular emphasis on the application of the methodology in the area of the performance and reliability modeling and analysis of the computer based systems, taking Test Facility system as a case study, is illustrated in this paper. This paper also describes the use of TimeNET (Timed Net Evaluation Tool), a software package for the modeling and evaluation of stochastic Petri nets with nonexponentially distributed firing times to evaluate performability. © 2012 IEEE.